Analisis Makna dan Nilai dalam Peribahasa Dawan - Selan, Dominggus Y. (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
The study aims to (1) describe the meanings in the Dawan proverbs, (2) describe the values in the Dawan proverbs, (3) formulate and describe the use of the Dawan proverbs in communication, and (4) formulate and describe the implications of the use of the proverbs by the speakers of the Dawan language. Semiotic and stylistic theories were used in the study. The theories were supported by theories of perspective in the forms of meaning theory, value theory, and cultural structure theory. The findings show that the Dawan proverbs consist of three parts: didactic meaning, religious meaning, and social meaning.